Marseillevirus in lymphoma: a giant in the lymph node. Issue 10 (October 2016) - Aherfi, Sarah; Colson, Philippe; Audoly, Gilles; Nappez, Claude; Xerri, Luc; Valensi, Audrey; Million, Matthieu; Lepidi, Hubert; Costello, Regis; Raoult, Didier
Summary: The family Marseilleviridae is a new clade of giant viruses whose original member, marseillevirus, was described in 2009. These viruses were isolated using Acanthamoeba spp primarily from the environment. Subsequently, a close relative of marseillevirus was isolated from the faeces of a healthy young man, and others were detected in blood samples of blood donors and recipients and in a child with lymph node adenitis. In this Grand Round we describe the detection of marseillevirus by PCR, fluorescence in-situ hybridisation, direct immunofluorescence, and immunohistochemistry in the lymph node of a 30-year-old woman diagnosed with Hodgkin's lymphoma, together with IgG antibodies to marseillevirus. A link with viruses and bacteria has been reported for many lymphomas. We review the literature describing these associations, the criteria used to consider a causal association, and the underlying mechanisms of lymphomagenesis. Our observations suggest that consideration should be given to marseillevirus infections as an additional viral cause or consequence of Hodgkin's lymphoma, and that this hypothesis should be tested further.